Innovation in Laparoscopic Inguinal Hernia Reparation – Initial Experiences with the Parietex Progrip Laparoscopic™ – Mesh - Klobusicky, Pavol; Feyerherd, Peter (Frontiers in Surgery, 2015)
Introduction: The Laparoscopic TAPP (transabdominal pre-peritoneal inguinal hernia repair) technique is becoming more widely and frequently used due to higher patient satisfaction and lower rates of both relapse and complications. Matherials and Methods: The role of the fixation of the mesh is especially important in regard to the endoscopic technique. The fixation of mesh thru penetrating techniques using staples, clips or screws is associated with a significantly increased risk of developing a post-herniotomy pain syndrome. In order to answer the question "fixation or no fixation of the mesh" the use of self-adhesive mesh is an optimal compromise. Conclusions: With the authors own operative technique consisting also of a standard pre and post-operative management, the self-adhesive mesh was proven to be extremely reliable. As no specific materials to fix the mesh were needed, the method was fast, simple and economical. We could also reduce the incidences of chronic inguinal pain in our patient population by using the self-adhesive mesh, without the risk of an increased recurrence rate in the observation period.